1992
DOI: 10.2527/1992.702576x
|View full text |Cite
|
Sign up to set email alerts
|

Forage systems for beef production from conception to slaughter: I. Cow-calf production

Abstract: Six year-round, all-forage, three-paddock systems for beef cow-calf production were used to produce five calf crops during a 6-yr period. Forages grazed by cows during spring, summer, and early fall consisted of one paddock of 1) tall fescue (Festuca arundinacea Schreb.)-ladino clover (Trifolium repens L.) or 2) Kentucky blue-grass (Poa pratensis L.)-white clover (Trifolium repens L.). Each of these forage mixtures was combined in a factorial arrangement with two paddocks of either 1) fescue-red clover (Trifol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…On irrigated alfalfa and tall wheatgrass pastures [A gropyron elongatum (Host) Beauv., = Elytrigia elongata (Host) Nevski], Lauriault et al (2005) found no differences in stocker cattle performance grazing monoculture alfalfa and the mixture of alfalfa with tall wheatgrass. Allen et al (1992) evaluated performance of cow–calf groups grazing mixtures of tall fescue–red clover, orchardgrass–red clover and orchardgrass–alfalfa in Virginia. They also found that pasture species mix had relatively minor effects on overall performance of cows and calves.…”
Section: Resultsmentioning
confidence: 99%
“…On irrigated alfalfa and tall wheatgrass pastures [A gropyron elongatum (Host) Beauv., = Elytrigia elongata (Host) Nevski], Lauriault et al (2005) found no differences in stocker cattle performance grazing monoculture alfalfa and the mixture of alfalfa with tall wheatgrass. Allen et al (1992) evaluated performance of cow–calf groups grazing mixtures of tall fescue–red clover, orchardgrass–red clover and orchardgrass–alfalfa in Virginia. They also found that pasture species mix had relatively minor effects on overall performance of cows and calves.…”
Section: Resultsmentioning
confidence: 99%
“…Fertilization rates were based on the estimated crop removal of 27.4 kg P ha j1 , assuming a forage yield of 7.84 t ha j1 and forage consisting of 3.49 mg g j1 P. The crop yield was based on yields measured for the area (Allen et al, 1992;Smith et al, 2005) and adjusted to site-specific limitations (i.e., northwest slope of site, shallow topsoil). As a result, 43.0 m 3 ha j1 dairy slurry, 24.7 m 3 ha j1 swine slurry, 14.1 t ha j1 beef manure, 2.3 t ha j1 poultry litter, and 62.7 kg ha j1 TSP were applied.…”
Section: Field Studymentioning
confidence: 99%
“…In a calf-to-beef system that couples backgrounding and finishing, more CH 4 is emitted from the forage-fed backgrounded phase than from the grain-based finishing phase and the cow herd is responsible for almost 70% of GHG emissions. The high proportion of CH 4 associated with the cow herd is because of the cow herd consuming a higher proportion of the feed in a calf-to-beef system, inherently low biological efficiency of the beef cow and the very high proportion of the cow herd's diet as conserved forage, pasture, range and crop residues rather than concentrates (Allen et al ., 1992; Verge et al ., 2008; Capper, 2011). The impact of roughage v .…”
Section: Introductionmentioning
confidence: 99%